The indigenous perspective of the meaning and treatment modalities of dysmenorrhea among the Batlokwa women of Limpopo province - Peu, Mmapheko Doriccah (University of Pretoria, 2021)
Thesis (PhD (Nursing))--University of Pretoria, 2020.